Building a cost function model to compare the efficiency of the serial sampling plan and the single sampling plan in qualitative control - Mohammed, Aseel Samir; Alwan, Asma Hussein; Hassoun, Intisar Obaid (Al-Adab Journal, 2021)
In this research a comparison between single and sequential S.P are performed. A special inspection cost model is built to compare between the two kinds of sampling, this model show that the sequential S. P is superior to the single S. P. All the notations needed for this purpose are explained.